THE ORGANIZATION OF JOINT ENTERPRISES IN THE REGIONS OF THE FERGHANA VALLEY AND THEIR ROLE IN THE ECONOMY OF THE COUNTRY (American Journal of Interdisciplinary Research and Development, 2022)
In the article, the establishment of joint ventures in the regions of Ferghana Valley and their role in the country’s economy is analyzed in detail with the help of primary sources and information from scientific literature.